EXPERIMENTAL INVESTIGATION OF WELD CHARACTERISTICS FOR A MIG WELDING WITH STAINLESS STEEL OF GRADE SS 410 - Jacob Bhoopalan S, Allan; S., Suresh kumar (International Journal of Psychosocial Rehabilitation, 2020)
This review focuses on the study of MIG welding on stainless steel 410. During this study, the properties of MIG are used to weld stainless steel 410. Welding is widely employed by manufacturing engineers and production personnel to quickly and effectively set up manufacturing processes for brand-spanking new products. The MIG welding parameters are the foremost important factors affecting the quality, productivity, and price of welding. This paper presents the influence of welding parameters like welding current, welding voltage, gas flow, wire feed rate, etc. on weld strength, ultimate lastingness, hardness of weld joints, and weld pool geometry of varied metal materials during welding. By using the DOE method, the parameters are often optimized, having the simplest parameter combination for target quality. The analysis from the DOE method can show the importance of the parameters because it gives an effect to vary the standard and strength of the product. Then various tests were conducted on the joints, such as tensile strength, bending test, microstructural test, and grain size test. And then, with the final results, the physical and mechanical properties were investigated.